Congenital Bronchobiliary Fistula: A Case Report and Literature Review - Zhen Bing; Rui Chen; Pengchao Xing; Yueyi Ren; Kefeng Hou (Frontiers Media S.A., 2021)
Congenital bronchobiliary fistula (CBBF) is a rare disease. Children with CBBF mostly have atypical clinical manifestations that can be easily missed. We report a case of a child with CBBF who was diagnosed with fistulography with the help of an endobronchial blocker and a fiberoptic bronchoscope. The CBBF was successfully removed by thoracoscopic surgery.